Analisis Variabel-Variabel yang Mempengaruhi Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018 - 2021 - Pratama Gilang Kotawa; R. Heru Kristanto; Sri Dwi Ari Ambarwati (Strata Business Review, 2023)
This research aims to determine the influence of profitability, liquidity, company size, growth opportunity, leverage, and COVID-19 on dividend policy. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for 2018 - 2021. The sample in this study was taken using a non-probability sampling technique, namely a purposive sampling technique. The number of selected pieces was 276-panel data of 69 companies (cross-section) and a 4-year time series. Hypothesis testing is carried out using panel data regression analysis with the Fixed Effect Model (FEM) regression model. The research results show that profitability, liquidity, company size, growth opportunity, leverage, and COVID-19 all influence dividend policy. Partially, profitability and liquidity have a positive effect on dividend policy, while power hurts dividend policy. Meanwhile, company size, growth opportunities, and COVID-19 did not affect dividend policy. Based on the results of the t-statistical test, 3 hypotheses were accepted, and 3 hypotheses were rejected. This research can provide practical contributions to investors or potential investors. Investors can use variable data that influences a company's dividend policy as a consideration for investing in the right company to get a return on investment in the form of dividends.